Field efficacy of two atoxigenic biocontrol products for mitigation of aflatoxin contamination in maize and groundnut in Ghana - Agbetiameh, D.; Ortega Beltran, A.; Awuah, R.T.; Atehnkeng, J.; Elzein, A.; Cotty, P.J.; Bandyopadhyay, Ranajit (Elsevier, 2020)
Biological control is one of the recommended methods for aflatoxin mitigation. Biocontrol products must be developed, and their efficacy demonstrated before widespread use. Efficacy of two aflatoxin biocontrol products, Aflasafe GH01 and Aflasafe GH02, were evaluated in 800 maize and groundnut farmers’ fields during 2015 and 2016 in the Ashanti, Brong Ahafo, Northern, Upper East, and Upper West regions of Ghana. Both products were developed after an extensive examination of fungi associated with maize and groundnut in Ghana. Each product contains as active ingredient fungi four Aspergillus flavus isolates belonging to atoxigenic African Aspergillus Vegetative Compatibility Groups (AAVs) widely distributed across Ghana. An untreated field was maintained for each treated field to determine product efficacy. Proportions of atoxigenic AAVs composing each product were assessed in soils before product application, and soils and grains at harvest. Significant (P < 0.05) displacement of toxigenic fungi occurred in both crops during both years, in all five regions. Biocontrol-treated crops consistently had significantly (P < 0.05) less aflatoxins (range = 76% to 100% less; average = 99% less) than untreated crops. Results indicate that both biocontrol products are highly efficient, cost-effective, environmentally safe tools for aflatoxin mitigation. Most crops from treated fields could have been sold in both local and international food and feed premium markets. Adoption and use of biocontrol products have the potential to improve the health of Ghanaians, and both income and trade opportunities of farmers, aggregators, distributors, and traders.